2017
DOI: 10.1016/j.jstrokecerebrovasdis.2017.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Function Testing in Patients with Acute Ischemic Stroke: An Observational Study

Abstract: In our opinion, platelet function testing could be potentially useful in monitoring the biological effect of antiplatelet agents. A substantial proportion of patients with stroke on ASA were "resistant", and the treatment with Clopidogrel was accompanied by even higher rates of unresponsiveness. Longitudinal studies are needed to assess whether aggregometry might supply individualized prognostic information and whether it can be considered a valid tool for future prevention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 50 publications
0
22
0
1
Order By: Relevance
“…Data from the literature provides information that the fact of taking ASA before stroke is relevant to the results obtained. Rosafio et al [23] and Sabra et al [24] showed significant differences in platelet reactivity between a group that took ASA for the first time in the acute phase of stroke and a group that had received ASA prior to stroke. In addition, some authors have shown that taking ASA before has a potential effect on the size of an ischemic focus [25].…”
Section: Discussionmentioning
confidence: 99%
“…Data from the literature provides information that the fact of taking ASA before stroke is relevant to the results obtained. Rosafio et al [23] and Sabra et al [24] showed significant differences in platelet reactivity between a group that took ASA for the first time in the acute phase of stroke and a group that had received ASA prior to stroke. In addition, some authors have shown that taking ASA before has a potential effect on the size of an ischemic focus [25].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent longitudinal observational study investigating platelet function by means of multiple electrode aggregometry in 624 stroke patients on anti-platelet therapy, 11% of patients with a stroke while on aspirin had high on-treatment platelet reactivity, and treatment with clopidogrel was accompanied by even higher proportions of unresponsiveness (36%), independent of the etiologic sub-type of stroke. 129 Rates of responsiveness to clopidogrel were not associated with CYP2C19 polymorphisms. In this context, Kunicki et al investigated the effect of aspirin on platelet function in 463 patients with stroke, transient ischaemic attack or acute coronary syndrome.…”
Section: Shortcomings Of Current Stroke Prevention and Treatmentmentioning
confidence: 96%
“…The response to aspirin was significantly better in combination with one of the two drugs used in this study and vice versa. Also, the combination of anticoagulant medication with a clopidogrel-type anti-aggregate potentiates the patient's response to treatment and improves the post-stroke hematoencephalic barrier activity in patient with severe heart disease [21,22].…”
Section: Resultsmentioning
confidence: 99%